Linear Integer Programming Theory, Applications, Recent Developments - Munapo, Elias (De Gruyter series on the applications of mathematics in engineering and information sciences., 2022)
This book presents the state-of-the-art methods in Linear Integer Programming, including some new algorithms and heuristic methods developed by the authors in recent years. Topics as Characteristic equation (CE), application of CE to bi-objective and multi-objective problems, Binary integer problems, Mixed-integer models, Knapsack models, Complexity reduction, Feasible-space reduction, Random search, Connected graph are also treated.